Meningkatkan Kuat Tekan Beton Fc’ 16,60 Mpa menggunakan Fly Ash dan Arang Batok Kelapa - Yusril Iza Mahendra; Edy Gardjito; Ahmad Ridwan; Haris Wicaksono (Faculty of Engineering, Kadiri University, 2021)
The science of concrete in the present era has developed. Research on efforts to improve the properties and performance of concrete has been carried out a lot. One of them is modifying a concrete mixture with fly ash as a substitute for some cement and coconut shell charcoal as a substitute for some sand. The chemical properties contained in fly ash are 80% in the form of silica and alumina. The purpose of this study was to determine the slump value and the compressive strength value of the test object added with fly ash with variations of 3%, 6%, 9% of the weight of cement, and 3% baroque coconut charcoal by weight of sand. This research method is experimental, which refers to the Indonesian National Standard with a test object cylinder size 15x30 cm totaling 12 samples tested at the age of 28 days with a quality plan fc'16.60 Mpa. The results showed that the highest slump value was obtained in the test object variation 3, namely 7 cm, while the average compressive strength of each variation has exceeded the quality of the plan with the highest value obtained in variation 2 with a compressive strength value of Fc'24.9 Mpa.